LEARNING BY EXPERIENCE WITH THE SCHOOL OF LIBRARIANSHIP URBAN TRANSPORTATION SYSTEM (SLUTS)/(APPRENDRE PAR LA PRATIQUE A L’AIDE DU SCHOOL OF LIBRARIANSHIP URBAN TRANSPORTATION SYSTEM (SLUTS)) - Piternick, Anne B.; Simmons, Peter (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF